(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
After more than five years in the making, since the creation by the President of the Federal Senate of the Commission of Jurists in charge of presenting a preliminary draft, the new Code of Civil Procedure is ready and should come into force on March 17, 2016. Let’s dispel the illusion that the new Code of Civil Procedure will transform Brazilian civil justice into the best justice in the world, as Minister of Justice Dino Grandi ufanistically proclaimed in the explanatory memorandum to the Italian Code of 1940. But I do think that a good procedural law can be an important factor in reversing the quantitative and qualitative deficit in the performance of Brazilian justice, if it is part of a public policy for resolving conflicts that tackles and equates excessive litigation, the indifference of the state to fulfilling its duty to respect citizens’ rights, the deficiencies in the training, selection processes and control of the performance of legal professionals, among others. There will be many difficulties in implementing and harmonizing this set of rules. It will certainly be a huge challenge that Brazilian civil justice will face on a daily basis once it comes into force. Perhaps the hermeneutic criteria established in Article 8 (human dignity, proportionality, reasonableness, publicity and efficiency) can contribute to this arduous task, especially if efficiency is not reduced to the simple pursuit of speed and productivity, but includes, as in the most modern models, broad access to justice for all those who need it and respect for equality of arms and equal legal protection for all jurisdictions.